Islamic Fiqh Principles For Worker Protection: Wage Determination and Payment - Nurcahyani, Sri; Ravena, Dey; Sundari, Rini Irianti (KARSA Journal of Social and Islamic Culture, 2025)
This study investigates Islamic jurisprudence principles concerning workers’ protection regarding wage determination and payment in Indonesia. Employing a juridical-normative approach, the research analyzes labor regulations, Islamic jurisprudential rules, and the concept of labor law. Data were collected through legal document analysis, Islamic literature review, and comparative studies and were analyzed qualitatively using descriptive-analytical methods. The findings indicate that Islamic jurisprudence principles, prioritizing justice, equality, and workers’ welfare, have been incorporated into Indonesian labor law through Law Number 13 of 2003 on Manpower and Government Regulation Number 51 of 2023 on Wages. Islam regards workers as equals to employers and prohibits the imposition of excessive workloads, delays in wage payments, and unjust treatment of workers. Similarly, Indonesian legislation prohibits employers from delaying wages and ensures workers receive fair compensation. The study underscores the significance of integrating Islamic principles with positive law to establish a more humane and equitable wage system that safeguards workers’ rights and promotes their welfare in Indonesia, particularly within the context of Subang Regency as an industrial area. This research contributes to a comprehensive understanding of legal protection for workers within the wage system by synthesizing the principles of Indonesian positive law and Islamic jurisprudence.